COPPER(II) COMPLEXES WITH NEW N-SUBSTITUTED SULFONAMIDES – SYNTHESIS, CRYSTAL STRUCTURE AND EVALUATION OF THE NUCLEASE ACTIVITY - BODOKI, Andreea; ALZUET-PIÑA, Gloria; BORRÁS, Joaquín; TOPALĂ, Tamara; HANGAN, Adriana; BORODI, Gheorghe; OPREAN, Luminița (Studia Universitatis Babeș-Bolyai Chemia, 2020)
Binary Cu(II) complexes of two new N-substituted sulfonamides, N-(pyridin-2-yl-methyl)biphenyl-4-sulfonamide (HL1) and N-bis-(pyridin-2-yl-methyl)biphenyl-4-4’-sulfonamide (H2L2), have been synthesized and characterized by X-ray diffraction, spectroscopic and electrochemical techniques. The structure of complex [Cu(L1)2] consists of a discrete monomeric Cu(II) species stabilized by π-π stacking interactions involving the pyridyl and phenyl rings of the coordinated ligands. In contrast, in the case of complex [Cu(L2)]n, each symmetrical sulfonamide structure coordinates two Cu(II) ions, giving rise to a polymeric chain. Upon coordination, CuN4 chromophores with the N-pyrydil atoms in trans position are generated, and the coordination geometry of both complexes can be best described as highly distorted square-planar. The ability of complex [Cu(L1)2] to promote DNA cleavage with ascorbate activation was also evaluated; the complex has a moderate nuclease activity, being able to partially cleave supercoiled DNA to nicked circular and linear DNA. We herein also report the evaluation of the nuclease activity of complex Cu2(N-(pyridin-2-yl)biphenyl-4-sulfonamidate)4, previously characterized in terms of structure by our group.